In vitro and in vivo evaluation of resveratrol and 3,5-dihydroxy-4′-acetoxy-trans-stilbene in the treatment of human prostate carcinoma and melanoma - Osmond, Gregory W. (2012)
BACKGROUND: Resveratrol (RESV) is a naturally occurring compound that may possess anti-cancer capabilities in both prostate carcinoma and melanoma. METHODS: The in vitro and in vivo cytotoxic activity of RESV and 3,5-dihydroxy-4′-acetoxy-trans-stilbene (4-ACE) was tested using cellular assays and a xenograft model. Five prostate carcinoma cell lines were used for in vitro evaluation. A melanoma cell line (Duke melanoma 738 [DM738]) and the prostate carcinoma line CWR22 were used for in vivo experiments. Mice were randomized to osmotic mini pumps with 200 μL of RESV (250 mg/mL), 4-ACE (335 mg/mL), or vehicle (50% dimethyl sulfoxide, 50% polyethylene glycol). Serum drug and metabolite levels were calculated by high-performance liquid chromatography with diode-array detection. Western blots were performed on treated tumors. Results were analyzed using a student’s t-test, analysis of variance, and the Mann–Whitney rank sum test. RESULTS: RESV and 4-ACE were cytotoxic in a time- and dose-dependent manner in all prostate carcinoma cell lines tested. Enhanced growth compared with controls was seen at the 24 h time point in four lines treated with RESV and two lines treated with 4-ACE (Ps < 0.048). In vivo, no difference in either tumor growth or postmortem tumor weight was detected in either DM738 (P = 0.555, P = 0.562) or CWR22 (P = 0.166, P = 0.811) xenografts treated with either drug. Serum drug levels did not correlate with tumor growth rates for any treatment group (all Ps > 0.11). Treated tumors demonstrated protein changes by western blot. CONCLUSION: Although in vitro data were promising, RESV and 4-ACE have limited potential as single agents in the treatment of prostate carcinoma and melanoma.